دلائل النبوةالقرآن الكريم – انشقاق القمر- (مجلة الواحات للبحوث والدراسات, 2015)
Praise be to God who created the universe in his ability, and deposited the secret of his wisdom, creates what he wants, and does what he wants, then prayer and peace upon our Prophet Muhammad seal of the prophets and messengers. After: the God did not create slaves in vain, and did not leave them in vain; but sent them prophets and messengers, and mode between him and them informing them orders and prohibitions, and consistence them the way of guidance and misguidance, though the subject of prophecy or prophecies of the great doors of faith; it faith in prophets of God-them Prayer and Salam a six pillars of faith, it is true faith slave even believe in God, His angels, His books, and His messengers, and the Last Day, and much good and evil, and of prophecy- as It is no secret- is the way to see favourable God and his exasperation, and orders and prohibitions, and close to him, What is for mercy, faith is the prophecy of conductive road to knowledge and love of God, and the route leading to the pleasure of Allah and his committee, and the way that leads to salvation from the punishment of God and win from the punishment of God and win forgiveness.Says "Shaykh al-Islam IbnTaymiyyah in this:" faith prophecy out of deliverance and happiness, it did not achieve this door was troubled by the door of guidance and misguidance, belief and disbelief, and did not distinguish between right and wrong".Prophecy mediation between the Creator and the creature in the Report has prescribed, and the Embassy between the king and his servants, and an invitation from the Merciful to his creation; to drive them out of the darkness into the light, and take them from this world to the narrow worldand the Hereafter capacity. And the need of people to acknowledge prophecy, most of their need for air, food and drink; Says "Shaykh al-Islam" the signs of the prophecy of the genus Godhead signs, where the visible and manifest for each one; memorable incidents, the all creatures in need to acknowledge the Creator and acknowledge Messengers". And on the above study are signs of prophecy, and show it -too- which increase the insured belief, perhaps the reason for the Islam of God wants to do good, and this is observed, the slave Muslim if passed inthe texts signs and signs on the prophecy of Prophet Muhammad, peace be upon him, The faith increases and strengthens the evidence,CadiAyyad says in a statement reason authored a book (el shafa recognize rights Prophet): "but accustomed to the people of his religion, who accept his call, who believe his prophecy, to be an affirmation in their love for him, and growth for their works, and that they may add faith to their faith".and these evidences -without doubt- are the largest proof that Muhammad is the Messenger from God; because God is not support lying, evidences prophecy are greater proof of the sincerity of our Prophet Muhammad, peace be upon him, with what God has honored from morals .Perhaps most important, it should be noted this extract are the following: First: that the evidences of prophecy or miracles of the prophets of all kinds, are an act of God, and no creature has the ability to find them on that face, which got him, and it appears evident in this sense offers us an indication in the Koran, and the miracle of splitting of the moon.Second: that God conducted on the prophets-Salam upon them and these signs or miracles; because they are subjects of argument and evidence, they serve as a witness to the proceedings in place of prophecy, and the purpose of them honor.Third: that the evidences of prophecy outweigh the dignities of the Patriarchs in quantity and quality, gender, type, Miracles carried out by prophecy, no doubt about it in the perceptions of the greatest mind of the dignities that are related to the mandate, and this is what entails the shrine of prophecy and the prophets, as is obvious. Fourth: I would recommend my fellow readers need to follow up this subject, and complete what is related sections nodosum, so Btelmus this contractual issues in Amadanha, which is written in the books of the scholars who are considered, than we have pointed out some of them, and I ask Allah to benefit with what you wrote, it is We calculated and yes, the agent, blessings and peace upon our Prophet Muhammad, and Praise be to Allah, the Lord of the Worlds